Pembelajaran Sejarah Peradaban Islam Melalui Online Game And Quiz - Abubakar, Isti'anah (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
History of Islamic civilization is a subject which gives advantages for all people who learn it, but unfortunately it can’t be realized in the results of learning. The impression of monotonous, static, bored, and saturated is responses that always appears when people learning history. Online gameand quiz is application that helped by web and internet access which enable students and teachers to learn History of Islamic civilization easily. This application indirectly make easy students and teachers to minimize the main problems in learning History of Islamic Civilization, they are complexity of material and students’ overfullness. As one alternative in learning History of Islamic civilization, this application still needs improvement. Sharing between teachers of History of Islamic civilization is defiitely expected to make this application better.Keywords : Online game and Quiz and learning of History